Hepatitis A Seropositivity among Children and Students Under 18 Years Old in Sulaimani Governorate-Kurdistan Regional Government - Hama, Salih A. (Sulaimani Journal for Pure and Applied Sciences, 2017)
To find the rates of anti-Hepatitis A Virus (HAV) IgG and IgM seropositivity among less than 18 years-old persons, 328 cases were tested by ELISA in Sulaimani Governorates, Iraqi Kurdistan region. It was observed that 47.86% cases were seropositive for anti-HAV IgG whereas only 16.15% were positive for anti-HAV IgM. Sex showed no significant effects on positive results for both IgG and IgM (p = 435, 0.891) respectively. The highest rate of anti- IgG seropositivity was among cases with more than 12 years-old (80.82%) while the highest rate for anti-IgM was among 5-8 years old (2.89%). The age showed noticeable effects on anti-IgG seropositivity (p = 0.000) unlike anti-IgM (p = 0.521). The child educational level also showed a significant effect on anti-IgG (p = 0.000) and anti-IgM (p = 0.0022). It was noticed that the well water has a significant effect on anti-IgM seropositivity (p = 0.027) among tested cases, while other sources showed no effects on the results (p>0.05). Family education showed significant effects on the anti-IgM seropositivity (p = 0.0022) unlike anti-IgG (p = 0.713). Moreover, it was concluded that the living places and family sizes showed significant effects on both anti-IgG and IgM seropositivity (p = 0.0022 and 0.0020) respectively for living places and (p = 0.0019 and 0.047) for family size). Socioeconomic status also significantly effective on anti-IgG (p = 0.0008) and anti-IgM seropositivity (p = 0.0078). The jaundice history showed valuable effects on anti-HAV IgG (p = 0.0207) and IgM seropositivity (p = 0.0017).
Keywords: AntiIgG; anti IgM; HAV; oralfecal route; socioeconomic status